Model Kepuasan Kerja sebagai Mediator Produktivitas : Studi pada Karyawan di Bandara Halim - Novita Damayanti; Vera Sylvia Saragi Sitio; Agus Purwo Wicaksono (Penerbit Goodwood, 2025)
Purpose : This study examines the effect of career development and work environment on employee productivity, with job satisfaction as a mediating variable. Methodology/approach: Conducted at Halim Kusuma Airport, the research used a quantitative approach with a census of 56 respondents. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. Results/findings: The findings reveal that career development and work environment significantly influence job satisfaction and employee productivity. Of the two, the work environment has the most dominant effect on job satisfaction, which in turn significantly affects productivity. Job satisfaction acts as an effective mediator, linking career development and work environment to productivity outcomes. Conclusions : These results indicate that achieving optimal employee productivity requires attention not only to formal organizational policies but also to how employees perceive their jobs and surroundings. A positive work environment contributes more strongly to satisfaction than career development, but both remain essential for fostering long-term motivation. Limitations: This research highlights the critical role of comprehensive human resource strategies that balance structural and affective aspects to enhance employee performance. Contribution: However, the study is limited by its focus on one sector, use of a cross-sectional design, and lack of analysis of specific work environment elements. Future research could adopt a longitudinal approach for deeper insights.